A blueprint for mass customisation in higher education. (23rd February 2015) - Hanna, Mark D.; Barman, Samir
Societal pressure for cost reduction has created an environment ripe for change in the value delivery system of higher education. When taken together, recent developments including massive open online courses (MOOCs), a strategy of flipping the classroom, and a changing focus from effective teaching to assurance of student learning, create an opportunity to address this societal pressure through mass customisation (MC). We use three elements of mass customisation (elicitation, process flexibility, and infrastructural logistics) and four approaches to MC (collaborative, adaptive, cosmetic, and transparent), to develop and discuss a blueprint for mass customisation in higher education.